Effects of health education tool on select epidemiological factors associated with adult obese urban slum women - Deepika Pradeep Vora; Pallavi S Shelke (Wolters Kluwer Medknow Publications, 2017)
Background: National Family Health Survey-3 (2005-2006) India, found that 14.8% of Ever-Married Adults (age 15-49 years) had Body Mass Index (BMI) in the ranges of overweight and obese; compared to 10.6% in the National Family Health Survey-2. These figures highlighted the fact that India already faces a dual burden of chronic malnutrition, i.e., obesity, besides undernutrition. Higher BMI, especially, increased abdominal fat is an important determinant of the development of diabetes. Objective: This study aims to understand the effect of health education on obesity status of adult women above the age of 20 years in an urban slum area. Methods: Community-based, interventional study, to assess select epidemiological factors associated with obesity-including measurement of anthropometry and assessing random blood sugar level; followed by an intervention (health education to only obese women by means of flip-chart); followed by a follow-up 6 months later. Results: About 22.6% women were found to be obese. Almost, all dietary and physical activity parameters as well as weight improved for the better after the intervention, and the change was statistically significant. Conclusions: This community based interventional study was able to understand certain factors associated with pathophysiology of obesity in slum dwelling adult women, and effectively documented a reduction in weight along with a change in their obesogenic practices postintervention.